PENERAPAN UNSUR-UNSUR PERBUATAN MELAWAN HUKUM TERHADAP KREDITUR YANG TIDAK MENDAFTARKAN JAMINAN FIDUCIA - Prihati Yuniarlin (Jurnal Media Hukum, 2012)
Fiduciary transfer of ownership is done through constitutum possessorium which means that the transfer is followed by an object control. The object of fiduciary assurance consists of chattels or moving objects and immovable objects which cannot be loaded with mortages, the transfer of chattels with real submission. As an effort to give a legal policy to the fiduciary assignor (creditor) and to fulfill the publicity principles, Government through the UUJF requires the creditor to register the fiduciary assurance in the Fiduciary Registration Office. That regulation is stated in the article 11 of UUJF. This study is a normative legal research with the research question as follow, “Can the elements of torts be implemented to the creditor or fiduciary assignee so that the creditoris considered doing the unlawful act?” The primary data are used in the study. The analysis results show that the elements of tort cannot be implemented to the creditor who does not register the fiduciary assurance in the Fiduciary Registration Office. Therefore, he is not considered doing the unlawful act.